2016
DOI: 10.1080/19434472.2016.1236143
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not paranoia when they are really out to get you’: the role of conspiracy theories in the context of heightened security

Abstract: Conspiracy theories have been seen as important supporting components in extreme political beliefs. This paper considers conspiracy theories in the counter jihad movement, an international network combining cultural nationalism with xenophobia towards Muslims. This paper evaluates the nature of conspiracy belief through the analysis of several key texts published by counter jihad activists, and of content published on a daily basis by three core websites. The findings show the Islamisation conspiracy theory to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…By casting even moderates as part of a conspiracy, the rhetoric is used to represent all Muslims as a potent threat to civic life and to justify radical, exclusionary politics—in this case the mass, forced deportation of Muslims. Lee () found that published statements by prominent figures in the so called “counter jihad” movement, which casts itself as the unofficial opposition to the Islamization of the West, seldom use conspiracy theories explicitly to justify extremist political action. Rather, they use conspiracy theories to create the ideological conditions for extremism and political violence.…”
Section: Definitionsmentioning
confidence: 99%
“…By casting even moderates as part of a conspiracy, the rhetoric is used to represent all Muslims as a potent threat to civic life and to justify radical, exclusionary politics—in this case the mass, forced deportation of Muslims. Lee () found that published statements by prominent figures in the so called “counter jihad” movement, which casts itself as the unofficial opposition to the Islamization of the West, seldom use conspiracy theories explicitly to justify extremist political action. Rather, they use conspiracy theories to create the ideological conditions for extremism and political violence.…”
Section: Definitionsmentioning
confidence: 99%
“…Cooperative learning process would encourage the students to study about positive sides form their friends. In turn, they would be conditioned within the learning process where a student is studying together with others in the atmosphere containing mutual respect, tolerant and understanding each other [26], [27].…”
Section: Resultsmentioning
confidence: 99%
“…Cooperative learning process would encourage the students to study about positive sides form their friends. In turn, they would be conditioned within the learning process where a student is studying together with others in the atmosphere containing mutual respect, tolerant and understanding each other (Lee, 2016;Lenssen, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%